2015
DOI: 10.15388/na.2015.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of the bacterial self-organization in a rounded container: The effect of dimensionality

Abstract: A bacterial self-organization in a rounded container as detected by bioluminescence imaging is mathematically modeled by applying the the Keller-Segel approach with logistic growth. The pattern formation in a colony of luminous Escherichia coli is numerically simulated by the nonlinear reaction-advection-diffusion equations. In this work, the pattern formation is studied in 3D and the results are compared with previous and new 2D and 1D simulations. The numerical simulation at transition conditions was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Consequently, many of the even more spectacular observations could be captured. An apparently chaotic pattern of E. coli merging/emerging events has been modelled via a PKS system in Baronas et al (2015). 10 Figure 4: An expanding pattern of spotted rings in the model (B1), where we set χ = 3, k 1 = 2, k 2 = 0.03, k 3 = 1, s = 2, k 4 = 0.5, k 5 = 1, k 6 = p = 0, D u = 0.1 and D v = 0.3.…”
Section: Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, many of the even more spectacular observations could be captured. An apparently chaotic pattern of E. coli merging/emerging events has been modelled via a PKS system in Baronas et al (2015). 10 Figure 4: An expanding pattern of spotted rings in the model (B1), where we set χ = 3, k 1 = 2, k 2 = 0.03, k 3 = 1, s = 2, k 4 = 0.5, k 5 = 1, k 6 = p = 0, D u = 0.1 and D v = 0.3.…”
Section: Modellingmentioning
confidence: 99%
“…for g(u) = (1 + tanh(k 2 (u − k 3 ))/2. Baronas et al (2015) for E. coli pattern formation, for bacteria (n), nutrient (succinate, s) and chemoattractant (aspartate, c): n t = ∇ · D n ∇n − χn∇c + k 1 n (1 − n/k 2 s) , c t = D c ∇ 2 c + k 3 n k 4 +n − k 5 c , s t = D s ∇ 2 s − k 6 n .…”
Section: Appendix a A Compendium Of Pks Models For Pattern Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one is derived from the behavior of bacteria in nature. [10][11][12][13][14][15] Keller and Segel's early research 16 suggested that the positive feedback loop between the signal release and chemotaxis of particles was the key to the formation of clusters. It has become a very popular direction to discuss the patterns formed by chemotactic particles under different chemical stimuli through the Keller-Segel approach.…”
Section: Introductionmentioning
confidence: 99%